Inflammation and tissue repair markers distinguish the nodular sclerosis and mixed cellularity subtypes of classical Hodgkin's lymphoma - Birgersdotter, A (Nature Publishing Group, 2009)
BACKGROUND: Classical Hodgkin's lymphoma (cHL), although a malignant disease, has many features in common with an inflammatory condition. The aim of this study was to establish the molecular characteristics of the two most common cHL subtypes, nodular sclerosis (NS) and mixed cellularity (MC), based on molecular profiling and immunohistochemistry, with special reference to the inflammatory microenvironment. METHODS: We analysed 44 gene expression profiles of cHL whole tumour tissues, 25 cases of NS and 19 cases of MC, using Affymetrix chip technology and immunohistochemistry. RESULTS: In the NS subtype, 152 genes showed a significantly higher expression, including genes involved in extracellular matrix (ECM) remodelling and ECM deposition similar to wound healing. Among these were SPARC, CTSK and COLI. Immunohistochemistry revealed that the NS-related genes were mainly expressed by macrophages and fibroblasts. Fifty-three genes had a higher expression in the MC subtype, including several inflammation-related genes, such as C1Qα, C1Qβ and CXCL9. In MC tissues, the C1Q subunits were mainly expressed by infiltrating macrophages. CONCLUSIONS AND INTERPRETATIONS: We suggest that the identified subtype-specific genes could reflect different phases of wound healing. Our study underlines the potential function of infiltrating macrophages in shaping the cHL tumour microenvironment.